TREATMENT OF HYPERKALEMIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE: A COMPARISON OF CALCIUM POLYSTYRENE SULPHONATE AND SODIUM POLYSTYRENE SULPHONATE - Nasir, Kiran; Ahmad, Aasim (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hyperkalemia is one of the most dreadful complications of chronic kidney disease (CKD). Medical management includes use of cation exchange resins to reduce the amount of excessive potassium from the body. Sodium polystyrene sulphonate (SPS) and calcium polystyrene sulphonate (CPS) are currently used for hyperklemia of CKD all over the world. The objective was to compare the efficacy and safety of two different cation exchange resins (CPS and SPS) in patients of CKD with hyperkalemia. Methods: This randomized control trial was done at the Kidney Centre, Post Graduate Training Institute (PGTi), Karachi, Pakistan between 15th January 2010 till 31st December 2010 to compare the efficacy and safety of, CPS and SPS in 97 CKD patients with hyperkalemia. The subjects were divided in two groups. Group-A received CPS while group-B received SPS. The data included symptoms, food recall, physical signs of volume overload and electrolytes. After receiving potassium binding resin for 3 days patients were evaluated for symptoms, weight gain, worsening of blood pressure and effect on electrolytes. Adverse events were recorded in an event reporting form. Results: Average potassium level pre resin was 5.8±0.26 in group-A and 5.8±0.6 in group-B, which reduced to 4.8±0.5 in group-A and 4.3±0.53 in group-B suggesting the efficacy of both drugs for treatment of hyperkalemia in CKD patients. Systolic blood pressure remains stable in both the groups while an increase in diastolic blood pressure was noticed in group-B patients (p-value 0.004). No major adverse effect occurred in both the groups. Conclusion: Both CPS and SPS can be used effectively for reducing hyperkalemia of CKD. CPS showed fewer side effects as compared to SPS. Keywords: Hyperkalemia, Chronic Kidney Disease, Cation exchange resin